Effect of ashing temperature on potassium nutrient content of various organic matter. Issue 4 (July 2021) - Anwar, A R; Ala, A; Kuswinanti, T; Syam'un, E
Abstract: Mineral ash fertilizer resulting from a burning process of plant wastes has the potential to replace or reduce the use of anorganic potassium fertilizers. Hence it can increase the availability of potassium for plants. This study aimed to determine the effect of ashing temperature on potassium nutrient content from kapok peels, banana stems, and coconut husks. The combustion temperature treatments were 300° C and 600°C for 3 hours into the muffle furnace and without ashing. Analysis of potassium content was conducted using the Atomic Absorption Spectrophotometer (AAS) method. The results showed that the temperature of 600°C gave the highest content of potassium from kapok peel (9.59%), the temperature of 300°C for banana stem (9.82%), while without ashing, the highest content of potassium was from the banana stem (8.20%). The organic matter that produces the highest potassium content was banana stem at an ashing temperature of 300°C, and the lowest was coconut husk at an ashing temperature of 600 °C.